Mediastinal Hydatid Cyst Rupturing into the Pleural Cavity Associated with Pneumothorax: Case Report and Review of the Literature - Mohd Shameem; Rakesh Bhargava; Zuber Ahmad; Nazish Fatima; Naveed Nazir Shah (Canadian Respiratory Journal)
Hydatid disease remains a serious health problem in Mediterranean countries. Living in a rural area is an important risk factor for the disease. Hydatid cysts are usually located in the liver, lungs and brain. Mediastinal hydatid disease is very rare and has been noted only anecdotally in the literature. The present article reports a case of a mediastinal hydatid cyst rupturing into the pleural cavity, which was associated with pneumothorax of the same side. The patient’s previous chest x-rays (posteroanterior and left lateral views) showed a well-defined mediastinal mass on the left side, and contrast-enhanced computed tomography of the thorax (taken a few days after the chest x-ray) showed multiple round-to-oval soft tissue opacities with partial collapse of the left lung. An indirect hemagglutination test for echinococcus was positive. Even after two weeks of intercostal tube drainage, the patient’s condition did not improve. During thoracotomy, multiple daughter cysts were found in the pleural cavity, and the diagnosis of a hydatid cyst was confirmed after histopathological examination.